Heterogeneity of the efficacy of the 23-valent pneumococcal polysaccharide vaccine caused by various underlying conditions of chronic pulmonary disease in older patients: prospective cohort study - Satoshi Morita; Satoshi Inoue; Takashi Sato; Yoshiaki Ishigatsubo; Shunsaku Mizushima; Yuji Watanuki; Tetsuji Kaneko; Naoki Miyazawa; Takeshi Kaneko; Yutaka Natsumeda (BMJ Open)
Objective To determine the ideal conditions for use of the 23-valent pneumococcal polysaccharide vaccine (PPV23) in older outpatients with chronic pulmonary diseases.Design Prospective cohort study.Participants 1378 outpatients with chronic pulmonary diseases ≥60 years of age.Intervention Participants were educated about PPV23, and those who responded affirmatively were vaccinated between August and November 2002. The participants who chose no intervention served as controls. The prevaccine period was defined as August 2001 to August 2002. Participants were followed for 2 years from December 2002 or until death.Main outcome measures Events of interest included the first episode of bacterial (including pneumococcal) pulmonary infection (primary endpoint) and death of any cause (secondary endpoint).Results Frequent episodes of pulmonary infection during the prevaccine period significantly decreased event-free survival during the 2-year observation period (p<0.001). Chronic respiratory failure was associated with a decreased event-free survival only when the pulmonary infection episode did not occur in the prevaccine period (p<0.001). No significant differences in event-free survival were observed between the vaccinated and unvaccinated group during analysis of the entire cohort. In the Cox proportional hazards regression model, event-free survival decreased significantly when pulmonary infection occurred in the prevaccine period. In the subgroup analysis, the first episode of bacterial pulmonary infection (but not death of any cause) was reduced significantly by PPV23 only in patients with chronic respiratory failure who had no episodes of pulmonary infection during the prevaccine period (p=0.019).Conclusion The efficacy of PPV23 against pulmonary infection and death of any cause might be unachievable if pulmonary infection occurs during the prevaccine period. PPV23 needs to be given to older patients with chronic pulmonary disease at an earlier time in which infectious complications in the lung have not yet occurred.